USING WHATSAPP AS A LEARNING MEDIA IN TEACHING WRITING - Hasliani Wibowo; Andi Muhammad Yauri; Uswatun Hasanah (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This paper discusses about the use of WhatsApp application as a learning media in teaching writing at the eleventh grade students of SMAN 2 Bone academic year 2020/2021. The study aimed to find out the teacher implementation of using the WhatsApp application in teaching writing at the eleventh grade of SMAN 2 Bone. In addition, also to find students' perceptions in using the WhatsApp application in teaching writing at the eleventh grade of SMAN 2 Bone. This research includes qualitative research with descriptive qualitative. Sampling in this research using purposive sampling technique, where the sampling technique was to took one teacher and ten students. The data was collecting by observation and interview. This research researcher analyzed data by reduction, display and drawing conclusions/verification. The result of the research that the teacher implementation used of WhatsApp application in teaching writing was carried out by utilizing the features of the application, however the use of the WhatsApp application was not optimal because it was recommended for teacher to make learning variations to attract students’ interest in learning. According to students the used of this application can help in collecting assignments easily.